WEB-BASED APPLICATION DESIGN FOR ADOPTION OF ABANDONED PETS - Nauli, Sukarno Bahat; Kusumawati, Kiki; Sitorus, Hernalom; Chafid, Nurul; Panjaitan, Bosar; Rahmatina, Izazih (Universitas Mercu Buana, 2024)
Abstract :This research is action research or also known as action research. Pejaten shelter is an organization engaged in the rescue of abandoned animals in the special area of the capital city of Jakarta and its surroundings. Abandoned animals accommodated in this place are dogs and cats. The number of adopted animals available reaches 1700-2000 animals. So far, the adoption process is still relatively difficult, namely by going through the stages directly and disseminating information only through the Instagram platform. then the shelter pejaten still uses routine reports on animals that have been adopted manually. Therefore the purpose of this research is to develop a web-based application that helps animal adopters to find animals for adoption, as well as helping adoption animal providers to disseminate animal adoption information, take care of online adoption needs, and facilitate the administration of animal adoption administration. The research method is divided into data collection methods, design methods, development methods, and evaluation methods. Data collection methods are in the form of surveys, interviews, observations, literature studies, and analysis of similar applications. The design method is divided into User Interface design methods and system design methods. The development method applied is the waterfall method which is divided into Requirement analysis, design, implementation, Testing, Maintenance. The results of the research are in the form of a web-based application that makes it easier for adopters and providers of adopted animals to find and disseminate information on animal adoption effectively, as well as to facilitate the management of online adoption and administration of animals.Keywords : application, adoption animal, design, waterfall